Investigating the Prevalence of Medication-induced Falls in Older Patients with Ischemic Stroke during Hospitalization - Puspita, Nanda; Verawati, Nurul; Hasbi, Fatwa (Clinical and Pharmaceutical Sciences Journal, 2025)
Stroke is among the most devastating neurological conditions that affect the elderly. In cases of acute ischemic stroke, hospitalised older patients will receive various regimens both for comorbidities and to prevent recurrent stroke. Multiple pathologies are the main reason geriatric patients receive large amounts of drug therapy. This phenomenon, known as polypharmacy, poses a significant issue in geriatric care. This requires monitoring, so it would not be potentially inappropriate medications that aggravate adverse drug reactions, including the risk of falls. Fall is a complex problem in old age, one of which is associated with medication use. This study aimed to identify potentially inappropriate medications according to the Beers Criteria list that are related to fall risk in older ischemic stroke patients in the hospital. A cross-sectional study used electronic health records (EHR) from 342 geriatric patients at the National Brain Centre Hospital, Jakarta, Indonesia. Systematic random sampling was employed to retrieve samples from the population. Demographic and clinical data were documented, and medications prescribed for patients were analysed. The majority of patients were aged 65 to 74 years (73.1%), male (57.9%), had a length of stay of 7 days (86%) and had comorbidities (94.4%). Medication categories that need monitoring for risk of falls are anxiolytics (14.04%), anticonvulsants (9.36%), antipsychotics (9.36%), and antidepressants (4.09%), and opioid analgesics (3.51%). There were no significant differences between patients with and without yellow wristbands who received drug regimens associated with a fall risk (p=0.674). Reviewing medication for older patients before discharge may be imperative to prevent the risk of falls due to taking potentially inappropriate medications. Keywords: Beers criteria, geriatric, medication-induced falls, stroke